Handbook of finance and development - Beck, Thorsten; Levine, Ross; Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
The Handbook of Finance and Development provides a thorough assessment of the existing research on the relationship between the financial system and economic growth. Containing chapters on theory, empirical work and historic accounts, this is the first Handbook to provide a comprehensive overview of the fields of finance and development. As leading researchers in the field the contributors analyse the emergence of, and innovations in, financial instruments, markets and intermediaries, providing commentary on how these components of financial systems shape resource allocation, poverty, income inequality and aggregate economic growth. They also explore the causes and consequences of financial fragility, the historic development of financial systems, and the regulatory and supervisory underpinnings of financial sector development. Further chapters examine financial development at both the aggregate and country levels and assess the degree to which individuals and firms can access financial services. Recent literature on the financial inclusion of households and enterprises is also analysed. The Handbook will be of great value to scholars and researchers who are interested in the fields of finance, development and financial inclusion. Throughout the chapters contributors highlight how insights drawn from research inform policy debates on the topics at hand, making this work a useful resource for policy makers and regulators.
Contents: Part I Theory and evidence on finance and growth -- 1. Financial development and innovation-led growth / Phillippe Aghion, Peter Howitt and Ross Levine -- 2. Financial structure, economic growth and development / Franklin Allen, Xian Gu and Oskar Kowalewski -- 3. Evidence on finance and economic growth / Alexander Popov -- Part II Historic accounts -- 4. Two centuries of finance and growth in the United States, 1790-1980 / Howard Bodenhorn -- 5. The financial system in Germany, 1800-1914 / Carsten Burhop, Timothy Guinnane and Richard Tilly -- 6. Finance and growth in the United Kingdom / Hans-Joachim Voth -- 7. East Asian financial and economic development / Randall Morck and Bernard Yeung -- 8. Sovereign commitment and financial underdevelopment in Nineteenth-century Brazil / William Summerhill -- Part III Finance, growth and stability -- 9. Finance and the real economy: evidence from the U.S / Allen Berger and Raluca Roman -- 10. Financial development, growth, and crisis: is there a trade-off? / Norman Loayza, Amine Ouazad and Romain Ranciere -- 11. The management and prevention of banking crises: lessons from recent experience / Patrick Honohan -- 12. Financial globalization: a glass half empty / Facundo Abraham and Sergio Schmukler -- 13. Technological change, financial innovation, and economic development / Thorsten Beck and Scott Frame -- Part IV Policies and institutions -- 14. Regulation and supervision and economic development / James Barth and Jerry Caprio -- 15. Bank ownership and economic development / Robert Cull, Maria Soledad Martinez Peria and Jeanne Verrier -- 16. What drives financial sector development?: policies, politics and history / Thorsten Beck -- 17. Endogenous political institutions and financial development / Thomas Lambert and Paolo Volpin -- Part V Access to finance -- 18. Financing SMEs and economic development / Meghana Ayyagari, Asli Demirguc-Kunt and Vojislav Maksimovic -- 19. Household finance and economic development / Asli Demirguc-Kunt, Leora Klapper and Dorothe Singer -- 20. Microfinance and economic development / Robert Cull and Jonathan Morduch -- Index.
Includes index.
Description based on print record.
Keywords: Economic development; Finance; Electronic books